Using Somatic, Auditory, Visualization, Intellectually (SAVI) Learning Model On Primary School To Enhance Science Learning Outcomes - Laili, Ilmi Nur; Gumala, Yosi; Awiria, Awiria; Syaodih, Ernawulan; Samsudin, Achmad (BRILIANT: Jurnal Riset dan Konseptual, 2023)
This research purposes to determine the influence of the Somatic Auditory Visualization Intellectually (SAVI) Learning Model on Science Learning Outcomes of 5th Grade Students on the Human Body Concept and to find out the results of students' Science learning on the Human Body Skeleton Material. The research design used was an experiment by means of a non-equivalent control group design and focusses in this examination were fifth grade primary school students. The investigation sample involved of two classes, to be exact the experimental class and the control group. In the experimental group there were 30 students, and in the control class there were 32 students. In obtaining the numbers, the researcher used the science learning achievement test method in the form of multiple-choice questions and documentation. The findings of the experiment indication that the SAVI learning model has an influence on the learning outcomes of natural science on the subject of the human body framework. The outcomes of analysis the assumption with the Mann Whitney test achieved from a posttest value of 0.000 <0.05 funds that H0 is rejected and Ha is accepted. The average of the experimental class that used the SAVI learning model was 79.7 better than the control class that was treated with Direct Instruction learning with an average of 62.4. The presentation of the SAVI learning model is expected to reassure students to be enthusiastically involved in solving problems and to consider analytically and critically.